Werner Herzog: Documentaries and Shorts - 4/6 - Herzog, Werner; Weisenborn, Christian; Keusch, Erwin; Schmidt-Reitwein, Jörg; Lachman, Ed; Klausmann, Rainer; Dickmann, Wolfgang; Peschke, Anton (Werner Herzog Film, 2006)
"Werner Herzog - Documentaries and Shorts" is as personal as it is comprehensive. Released by Werner Herzog Films, the six-disc box set includes nearly all of Herzog's documentaries and shorts completed during the first thirty-one years of his career, from his first experimental short "Herakles" in 1962, to his 1993 documentary about faith and superstition in "Russian, Bells from the Deep". Rounding out the set is Herzog's 1999 documentary "Wings of Hope". [www.dvdtalk.com]
Keywords: DVD-Video